2020
DOI: 10.1186/s40563-020-00124-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on the behavior of teak wood adherends bonded joints

Abstract: IntroductionNowadays, scientific communities and industries are looking for alternative materials to the synthetic composites and metals, as these materials are non-degradable, limited in quantity, hazardous to nature and costly [1,2]. Hence many researchers are attracted towards natural materials (e.g. wood) for various applications, such as construction, furniture, decorative products, sports items and many others. Wood is one of the most important materials and widely used since the old era, as it is easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This was assumed to be due to the removal of hemicellulose, the depolymerization of hydrocarbons and lignin, or the increase in the degree of crystallinity of the amorphous cellulose [18]. While conducting research with Indian teak boards, BUDHE et al [19] found that the heat treatment decreased the wood surface wettability. In research with Pinus caribaea, SANTOS and SILVA [20] observed that the process of thermal modification influenced the wood's physical properties, promoting a reduction in the equilibrium moisture, a lower hygroscopicity, and greater dimensional stability, in addition to evidencing the notoriety of the material subjected to a higher temperature.…”
Section: Bulk Density and Moisture Contentmentioning
confidence: 99%
“…This was assumed to be due to the removal of hemicellulose, the depolymerization of hydrocarbons and lignin, or the increase in the degree of crystallinity of the amorphous cellulose [18]. While conducting research with Indian teak boards, BUDHE et al [19] found that the heat treatment decreased the wood surface wettability. In research with Pinus caribaea, SANTOS and SILVA [20] observed that the process of thermal modification influenced the wood's physical properties, promoting a reduction in the equilibrium moisture, a lower hygroscopicity, and greater dimensional stability, in addition to evidencing the notoriety of the material subjected to a higher temperature.…”
Section: Bulk Density and Moisture Contentmentioning
confidence: 99%